2013
DOI: 10.1159/000343394
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Presentation and Presence of DNA Adducts and p53 Mutations in Patients with Endemic Nephropathy - an Environmental Form of the Aristolochic Acid Nephropathy

Abstract: Background: Endemic nephropathy (EN) and associated urothelial cell cancers (UUC) are an environmental form of aristolochic acid nephropathy where the most probable rout of ingestion of aristolochic acid (AA) was made by bread contaminated with AA, leading to chronic dietary intoxication. Clinical courses of three members of the same family, similarly exposed to toxin, who exhibited different clinical courses of the disease are presented. Methods: Questionnaires on AA exposure were taken. Tissue samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, the histological staining of the kidney was only conducted on the left kidneys. While several reports mentioned that the two kidneys responded differently towards the injury [17]. us, the histological changes of the right kidneys need further studies to confirm.…”
Section: Discussionmentioning
confidence: 93%
“…However, the histological staining of the kidney was only conducted on the left kidneys. While several reports mentioned that the two kidneys responded differently towards the injury [17]. us, the histological changes of the right kidneys need further studies to confirm.…”
Section: Discussionmentioning
confidence: 93%
“…miR-584 has anti-inflammatory effects that modulate AA functions [61]. Subsequently, miR-584 regulated pathways such as MAPK signalling pathways, pathways in cancer, Wnt signalling pathways, p53 signalling pathways, and TGF-beta signalling pathways are associated with AAN [9, 53, 6266]. Thus, has-miR-33a and has-miR-584 may be biomarkers for the diagnosis and prognosis of AAN, which must be confirmed in further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that AA stimulated the p53 pathway, mediating TEC apoptosis in acute AAN [7, 8]. Moreover, AA-DNA adducts are an AA exposure marker and risk factors of AA nephropathy-associated cancer [9]. AA commonly induces tumours in the renal cortex, renal pelvis and urinary bladder.…”
Section: Introductionmentioning
confidence: 98%
“…Ochratoxin A (OTA) was mostly investigated but in 2006 the EU Committee on Food Safety reported that there was no convincing evidence from human epidemiology to confirm the association between OTA exposure and the prevalence of BEN or UTUC. 27 This conclusion was based on several important facts: (1) OTA is present in food worldwide; (2) significant overlap was found in the average OTA contamination levels of relevant food categories between BEN and non-BEN areas; (3) higher average blood OTA concentrations 48 ; small kidney: length 7 cm, weight 26 gram, smooth surface) (first row, left). Photomicrograph of gradual decrease in fibrosis severity and tubular atrophy from outer-to-inner cortex (hematoxylin-eosin, £40) (first row, right).…”
Section: Epidemiology and Etiology Of Benmentioning
confidence: 99%